PROBLEMATIKA PENEGAKAN HUKUM TINDAK PIDANA KORUPSI - Ely, Kasman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : This research discusses about the Problem of establishment of corruption crime eradication law as respond to corruption problem which increasingly complex occurs in Indonesia. The purpose of this writing and research is to provide an overview and analysis about the problem of corruption crime eradication. The method used is a normative juridical approach focusing on literature studies and legal regulatory analysis. The results of this study found that there are problems in enforcing the law on corruption crimes, namely the disparity in decisions against Corruption Defendants in the same case, unapplied the reverse burden of proof, there is a threat of a very light minimum sentence for State Officials or State Civil Apparatus who committed Corruption, such as 1 (one) year in prison, a minimum fine of 50 million, and the lack of legal awareness of the Indonesian people regarding the latent dangers of Corruption. Keywords: Corruption, Law Enforcement, Corruption Crime, Corruption Problems, Causes of Corruption.